Symbolic Violence Against Women in Medan’s Patriarchal Culture - Ariftha, Annisa; Azhar, Anang Anas (SCAD Independent, 2023)
The study on symbolic violence against women is limited. There is still a significant degree of suspicion and stigma in society around the notion that women are weak and helpless compared to men and that women are continually the victims of patriarchal symbolic violence in terms of language, social economics, and others. This research aims to investigate how and why symbolic violence is performed against women in patriarchal cultures, the kinds of symbolic violence against women, the determinants of symbolic violence in this instance, and the effects of linguistic-symbolic violence on women in Medan Tembung. This qualitative research included seven individuals between the ages of 15 and 35. Observations and interviews were employed to collect data for this investigation. The acquired data was then examined using sociological methodologies to disclose the field phenomena and interview outcomes precisely. Furthermore, this research employs the theory of Pierre Bourdieu to comprehend symbolic violence in society. This study's results demonstrate that symbolic violence persists in society, particularly in meetings and in the form of language. The results of this research support this concept by providing evidence of symbolic violence in the form of language or particular terminology that women are not permitted to use, although males are permitted to do so, and which seem to be prevalent in daily life.